Desenvolvimento de sistemas adesivos autocondicionantes bioativos: caracterização físico-química, análise da interface de união e bioatividade - CARVALHO, Edilausson Moreno (2019)
Objective: To develop and evaluate physicochemical, mechanical and biological properties of experimental self-etching adhesive systems containing microparticles of different bioactive glasses (45S5 and a niobium-based experimental glass - NbG). Materials and methods: The 45S5 and NbG glasses were dry milled (in a planetary mill) to obtain microparticles, approximately 5 µm in size. Two-step experimental self-etching adhesive systems containing 5%, 10% and 20% (% weight) of the two bioactive glasses were developed. The microparticles were added to the hydrophobic (bond) portion of the materials. In addition, a particle free experimental adhesive (experimental control) and Clearfil SE Bond adhesive system (commercial control) were also used. Bond samples were made and materials were evaluated for degree of conversion, tensile strength, solvent softening, radiopacity, water sorption and solubility, pH change and ionic release. Forty-eight human third molars were selected, prepared and restored with the adhesive systems for microtensile bond strength and nanoinfiltration evaluation after two storage periods: 24 hours and one year. Bioactivity was evaluated after immersion of bond samples for 28 days in simulated body fluid solution (SBF). The surface of these samples was analyzed by Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR / ATR) and X-ray Diffraction (XRD) for identification and characterization of bioactive precipitates. Data were submitted to ANOVA, Holm-Sidak post-test (α = 0.05) and descriptive statistics. Results: After the dry milling process, the 45S5 and NbG microparticles had an approximate average size of 4 and 3.3 µm, respectively. The addition of the two bioactive glasses did not negatively influenced the degree of conversion, tensile strength and solvent softening of the adhesives. The adhesive system containing NbG 20% presented the highest radiopacity values among all materials. The incorporation of 45S5 significantly increased the water sorption and solubility values of the adhesive systems, alkalized the solutions and allowed the release of large amounts of calcium ions at all concentrations. On the other hand, the NbG did not influenced the water sorption and solubility values of the adhesives and pH of the solutions, with the release of small amounts of phosphorus ions, regardless of the concentration. After one year of storage, the adhesives containing bioactive glasses were able to keep stable values of bond strength and nanoinfiltration at all concentrations. After 28 days of SBF immersion, groups containing 45SS were able to present bioactivity through precipitation of hydroxyapatite and calcium carbonate. No deposition of mineral precipitates could be observed in groups containing NbG. Conclusion: The incorporation of bioactive glass microparticles in self-etching adhesive systems is able to promote the creation of more degradation-resistant interfaces. The addition of 45S5 glass in these adhesive systems was able to promote bioactivity through the formation of a hydroxyapatite layer in the surface.